ADMINISTRATIVE AND LEGAL PRINCIPLES OF THE ACTIVITIES OF ENTITIES THAT ENSURE THE STATE REGISTRATION OF REAL RIGHTS TO REAL ESTATE OBJECTS THAT WILL BE CONSTRUCTED IN THE FUTURE - Kohut, Bohdan (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to study the administrative and legal basis of the activity of entities that provide state registration of property rights to real estate objects that will be built in the future. Research methods: documentary analysis, generalization of legal information. Results: the article discloses the administrative-legal status of entities that ensure the state registration of property rights to real estate objects that will be built in the future - the notary and the state registrar of rights, as entities of administrative-legal relations. In accordance with certain provisions of the article, the specifics of the status and powers of the notary and the state registrar in relation to matters of exercise of authority in the field of state registration of rights, in particular during the implementation of registration proceedings regarding the state registration of rights to real estate objects, are determined, that will be built in the future, as well as focusing on the features of the powers of the notary and the state registrar, with which the state authorized them to perform the relevant functions, as well as those defined by the legislation, in order to exercise within the limits of the powers granted to ensure the provision of high-quality administrative services and ensure citizens to exercise their guaranteed rights. In addition, attention was paid to the general theoretical principles that apply to the subjects of administrative-legal relations, and the role of these principles during the exercise of their powers by the notary and the state registrar directly during the state registration of rights to real estate objects to be built in the future and compliance with legislation during each component of the registration process. It is also determined that when exercising the powers granted by the state, notaries and state registrars observe the general principles of state registration of property rights to immovable property and their encumbrances and have the authority to take appropriate actions in the relevant information system (register) directly in the State Register of Property Rights to Real Estate. The peculiarities of the administrative-legal status of the notary and the state registrar in administrative-legal relations and directly in interaction with other participants (entities) during the implementation of registration proceedings regarding the state registration of property rights to real estate objects that will be built in in the future. In addition, attention was paid to the legal status of individuals and legal entities who, when applying to the notary and state registrar for the exercise of their rights. The advantages and disadvantages of the administrative-legal regulation of the registration activity of notaries and state registrars during the implementation of registration proceedings regarding the state registration of property rights to real estate objects that will be built in the future are identified.